Access to 911 Recordings: Balancing Privacy Interests and the Public's Right to Know about Deaths. Issue 3 (3rd July 2019) - Coyle, Erin K.; Whitenack, Stephanie L.
Abstract : Publicly disclosing 911 recordings sometimes sheds light on important matters of public interest. Nonetheless, some state statutes, court opinions, and attorneys general opinions recognize surviving family members' privacy rights may be harmed by publicly disclosing such recordings when they involve deaths. States take a variety of approaches to balance privacy interests with interests in disclosing 911 records. In some instances, states have found that the likelihood of harm to privacy justified exempting from disclosure 911 call records. This article recommends that states require in camera court review of 911 call recordings related to deaths for judges to assess whether releasing the records would serve a public interest that outweighs interests in nondisclosure.